2013
DOI: 10.1016/j.shaw.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment Suggests Exposure to Lung Cancer Carcinogens in a Painter Working in an Automobile Bumper Shop

Abstract: A 46-year-old man who had worked as a bumper spray painter in an automobile body shop for 15 years developed lung cancer. The patient was a nonsmoker with no family history of lung cancer. To determine whether the cancer was related to his work environment, we assessed the level of exposure to carcinogens during spray painting, sanding, and heat treatment. The results showed that spray painting with yellow paint increased the concentration of hexavalent chromium in the air to as much as 118.33 μg/m3. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
2
9
0
1
Order By: Relevance
“…Chromate, lead, and Sr have been found in paint samples (solvent-based) that were collected from a shop that had had a case of occupational lung cancer [ 19 ]. Lead, Cr(6+) (total Cr), and Sr levels in orange-yellow, yellow, and bright yellow paints have been to be 173,568, 78,105, and 186,437 ppm; 18,295 (43,416), 14,085 (14,085), and 10,935 (36,302) ppm; and 46, 141, and 267 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromate, lead, and Sr have been found in paint samples (solvent-based) that were collected from a shop that had had a case of occupational lung cancer [ 19 ]. Lead, Cr(6+) (total Cr), and Sr levels in orange-yellow, yellow, and bright yellow paints have been to be 173,568, 78,105, and 186,437 ppm; 18,295 (43,416), 14,085 (14,085), and 10,935 (36,302) ppm; and 46, 141, and 267 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Lead, Cr(6+) (total Cr), and Sr levels in orange-yellow, yellow, and bright yellow paints have been to be 173,568, 78,105, and 186,437 ppm; 18,295 (43,416), 14,085 (14,085), and 10,935 (36,302) ppm; and 46, 141, and 267 ppm, respectively. However, only trace levels have been detected in eco-friendly paints [ 19 ]. The results of this investigation are consistent with these findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient was also found not to be trained in correctly wearing the dust mask. Overall fit factors of the general dust mask which is currently available in the domestic market were not outstanding for workers who are not trained in their use (Kim et al, 2013). Such dust mask use does not provide sufficient prevention of exposure to hexavalent chromium.…”
Section: Discussionmentioning
confidence: 97%
“…In South Korea, Kim et al (2013) reported a lung cancer patient who performed painting in an automobile bumper shop and identified an association with exposure to hexavalent chromium (24 µg m -3 ) during spraying gray and yellow paints, even though the workload of painting with yellow associated with hexavalent chromium was minor on a daily basis. In addition, NIOSH found painters who performed multiple tasks, such as spraying, sanding and clean up, were exposed to high levels of hexavalent chromium with a 16 µg m -3 eight-hour TWA (NIOSH, 2013).…”
Section: Discussionmentioning
confidence: 99%